Baseline heart rate variability predicts placebo hypoalgesia in men, but not women - Joy Krecké; Angelika M. Dierolf; Katharina M. Rischer; Fernand Anton; Marian van der Meulen (Frontiers in Pain Research, 2023)
IntroductionPlacebo hypoalgesic effects vary greatly across individuals, making them challenging to control for in clinical trials and difficult to use in treatment. We investigated the potential of resting vagally-mediated heart rate variability (vmHRV) to help predict the magnitude of placebo responsiveness.MethodsIn two independent studies (total N = 77), we administered a placebo paradigm after measuring baseline HRV. In Study I, we delivered heat pain to the forearm, on skin patches treated with “real” and “control” cream (identical inactive creams). In Study II, electrical pulses to the forearm were modulated by sham transcutaneous electrical nerve stimulation. We combined data from both studies to evaluate the relationship between vagally-mediated HRV (vmHRV) parameters and the placebo response size, while also assessing sex differences in this relationship.Results and DiscussionThis revealed a positive association between vmHRV and the degree of pain relief, and this effect was driven by men. These results not only reveal new insights into the (sex-specific) mechanisms of placebo hypoalgesia, but also suggest that measuring vmHRV may be helpful in predicting placebo responsiveness. Given that placebo hypoalgesic effects contribute substantially to treatment outcomes, such a non-invasive and easily obtained predictor would be valuable in the context of personalized medicine.